An Individualized Approach to Neuroplasticity After Early Unilateral Brain Damage - Gaberova, Katerina; Pacheva, Iliyana; Timova, Elena; Petkova, Anelia; Velkova, Kichka; Ivanov, Ivan (Frontiers in Psychiatry, 2019)
Introduction: Reorganization after early lesions in the developing brain has been an object of extensive scientific work, but even growing data from translational neuroscience studies in the last 20 years does not provide unified factors for prediction of type of reorganization and rehabilitation potential of patients with unilateral cerebral palsy due to pre/perinatal insult. Aim: To analyze the type of motor, language and sensory brain reorganization in patients with right-sided cerebral palsy due to pre-/perinatal isolated left-sided brain lesions taking into consideration the type (cortico-subcortical or periventricular) and extent (grey and white matter damage) of the lesion, etiology, comorbidity and other postnatal factors, that could have played a role in the complex process of brain plasticity. Material and methods: Eight patients with unilateral right cerebral palsy were included in the study. The individual data from fMRI of primary sensory, motor and language representation were analyzed and compared with respective comprehensive etiological, clinical and morphological data. Patients were examined clinically and psychologically, and investigated by structural and functional 3T GE scanner. A correlation between the type and extent of the lesion (involvement of cortical and subcortical structures), timing of lesion, type of reorganization (laterality index), and clinical and psychological outcome was done. Results: Significant inter-individual diversity was found in the patient group predominantly in the patterns of motor reorganization. Patients with small periventricular lesions have ipsilesional representation of primary motor, sensory and word generation function. Patients with lesions involving left cortico-subcortical regions show various models of reorganization in all three modalities (ipsilesional, contralesional and bilateral) and different clinical outcome that seem to be impossible for prediction. However, patients with UCP who demonstrate ipsilesional motor cortical activation have better motor functional capacity. Conclusion: The type and size of the pre-/perinatal lesion in left hemisphere could affect the natural potential of the young brain for reorganization and therefore the clinical outcome. Much larger sample and additional correlation with morphological data (volumetry, morphometry, tractography) is needed for determination of possible risk or protective factors that could play a role in the complex process of brain plasticity.